PENGARUH PEMASARAN MEDIA SOSIAL DAN PENJUALAN PRIBADI TERHADAP KESADARAN MEREK - Mulya, Visakha; Handrito , Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2023)
The twentieth-century technological development has brought innovation in financial sector through the emergence of financial technology, colloquially referred to as fintech. One of the peer-to-peer lending companies in Indonesia is PT SimpleFi Teknologi Indonesia, or AwanTunai. According to Techinasia, fintech startups have grown rapidly during the last few years, but most consumers do not realize it. The objective of this quantitative explanatory research is to identify the partial effects of social media marketing and personal selling on brand awareness. From the population of Indonesian entrepreneurs who know about AwanTunai, 110 people were selected as the respondents through the use of purposive sampling. The data was harvested online via Google Forms and was analyzed using multiple linear regression in Statistical Product and Service Solution (SPSS) 24,0 for Windows. This study finds that social media marketing and personal selling positively and significantly influence the brand awareness. Therefore, the social media marketing and personal selling organized by AwanTunai have created brand awareness among entrepreneurs. However, the company needs to improve their consistency in posting content in social media, promote openness in its communication, and provide trainings for its sales representatives so that the awareness of entrepreneurs to AwanTunai increases.